Using Kindle a complete guide to Amazon's revolutionary wireless reading device - Cheshire, Jim (Que, 2009)
Introducing Using Kindle . Meticulously researched and painstakingly written to be the one Kindle resource you can't live without, Using Kindle is a thorough guide covering all aspects of the Kindle, including the new Kindle 2 and DX models, and is designed to teach you everything you need to know. Using Kindle was written for all Kindle users, even those who have absolutely no technical expertise and are inexperienced in using a computer. Here are just a few of the many things you'll learn in this book: -- Tips and tricks to help make your basic Kindle reading experience more enjoyable. -- Coverage of Kindle DX's native PDF support and accelerometer - it will automatically switch from portrait to landscape when you turn it! -- Details on Amazon's WhisperSync service for owners of multiple Kindles, an iPhone, or an iPod touch. -- Details on where you can locate free books as well as tips on how you can search for hard-to-find free books. -- How you can use free software to convert books and edit author name, title, and other information. -- The best ways to take advantage of the Kindle's built-in Web browser, including how to use email, blog readers, eBay, social networking, and even manage your Netflix movie queue. -- How to listen to music while you read. -- How to listen to podcasts on your Kindle (and how to make the Kindle automatically remember your current place in your favorite podcast.) -- A comprehensive FAQ on the Kindle using carefully researched questions asked by Kindle users. -- Innovative ideas on using the Kindle for an information-storage device. -- Much, much more! Buy Using Kindle today and spend more time reading what you want and less time trying to figure out the Kindle.
Print version record
Keywords: Kindle (Electronic book reader); Kindle (Lecteur électronique)